Utilization of fermented Cassava Leaf (Manihot utilisima ) meal In diets On Growth of Jelawat (Leptobarbus hoeveni) - Afan Sholeh; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study was to know the amount of fermented cassava leaf meal the diets on growth, feed efficiency, feed digestibility and protein retention of Jelawat (Leptobarbus hoeveni.). Five isonitrogenous (30% crude protein) experimental diets was formulated to contain 0, 10, 15, 20, and 25% fermented cassava leaf meal and 100, 90, 85, 80 and 75% soybean meal (P0,P1,P2,P3,P4, respectively).Completely randomized design (CRD) was used in this exsperiment.The result showed that a diet containing 10% fermented cassava leaf meal and 90% soybean meal (P1) support a good specific growth rate (1.61%/day), feed efficiency (20.70%), feed digestibility (42.01) and protein retention (13.62%). It this concluded that soybean meal can be substituted with 10% fermented cassava leaf meal in the diets for jelawat.Key word: cassava leaf, diet, fermentation, growth, Leptobarbus hoeveni